Characterizing Electrolyte and Platinum Interface in PEM Fuel Cells Using CO Displacement. Issue 2 (13th December 2016) - Garrick, Taylor R.; Moylan, Thomas E.; Yarlagadda, Venkata; Kongkanand, Anusorn
Abstract : Relatively large O2 transport resistance at the ionomer and Pt interface has been thought to be responsible for the large performance loss at high power for a low Pt loading proton-exchange-membrane fuel cell. A facile method to characterize the interface in the fuel cell electrode is needed. In this study, the CO displacement method was explored on polycrystalline Pt and carbon-supported Pt nanoparticles. The displacement charge coverages were used to quantify the adsorption of perchlorate, sulfate, and perfluorosulfonic acid ionomer. The application of this method in a fuel cell electrode was demonstrated.